Impact of molecular linker size on physicochemical properties of assembled gold nanoparticle mono-/multi-layers and their applicability for functional binding of biomolecules - Krikstolaityte, Vida (2021)
In this work the impact of molecular inter-linker size on gold nanoparticle (AuNP) mono-/multilayer structural properties, density and homogeneity has been investigated. These characteristics are of great importance for functional binding of biomolecules. Positively charged high or low molecular weight inter-linkers, poly-L-lysine (PLL) or N-(6-mercapto)hexylpyridinium (MHP), were used to attach negatively charged AuNPs on a planar gold surface as well as to further interlink into a multilayer structure via layer-by-layer deposition. The inter-particle interaction within the assembled AuNP films was adjusted by the ionic strength in the AuNPs dispersions. The AuNP layer density and structural/viscoelastic properties were evaluated by the quartz crystal microbalance with dissipation (QCM-D) technique. The validity of the commercial Voigt model, specifically developed for quantitative QCM-D data analysis of homogeneous viscoelastic films, was evaluated by a model independent analysis when comparing the assembled AuNP films with a homogeneous layer of a mucin from bovine submaxillary glands. Both AuNP mono- and multilayers, attached/interlinked via long flexible PLL molecules assembled to denser and more soft/viscous structures compared to those interlinked by short MHP compounds. Thus, PLL-interlinked AuNP mono-/multilayer structures were further investigated as a platform for laccase enzyme functional adsorption via qualitative assessment of bioelectrochemical characteristics of the enzyme.